Nanostructured tin oxide: synthesis and gas-sensing properties - Niranjan, R. S.; Hwang, Young Kyu; Kim, D. K.; Jhung, S. H.; Chang, J. S.; Mulla, Imtiaz S. (Materials Chemistry and Physics, 2005)
Pure and Ru-doped nanostructured SnO2 sensing materials were synthesized using a modified Pechini route. Incorporation of Ru in SnO2 results in the reduction of particle size (8.3 nm) compared with that of the pure SnO2 (28.2 nm). Moreover, the sensor exhibited a reasonably good sensitivity towards both H-2 and liquified petroleum gas (LPG). The effect of Ru incorporation, operating temperature, and gas concentration on the structure, morphology, and sensitivity is discussed using the results of X-ray diffraction (XRD), and scanning electron microscopy (SEM) along with sensing performance. © 2005 Elsevier B.V. All rights reserved.
Keywords: hydrogen and hydrocarbon sensor; Nanostructure; ruthenium; tin oxide